Induction of resistance in rice plant against sheath blight with non-conventional chemicals - and A.K. ROY, ASHOK BHATTACHARYYA (Indian Phytopathology, 2002)
Twenty one non-conventional chemicals each at two concentrations in wet seed treatment, root-dip treatment and spray treatment were tested against sheath blight of rice caused by Rhizoctonia solani. Sodium selenite at 10’ M,zinc sulphate at 104M, lithium sulphate at 104M, calcium nitrate at 10Â·1M,sodium fluoride at 10Â·3M and ferric chloride at 10Â· 4M could check the disease in excised rice leaves as well as in standing plants. When tested by ’poison food technique’, these chemicals showed no in vitro fungitoxicity at their effective concentrations. Highest efficacy was recorded when the combination of all three methods was used, stage by stage.